Analysis of Cash Holding and Firm Size on Firm Value in Coal Mining Companies Listed on the Indonesia Stock Exchange - Mursalini, Wahyu Indah; Sriyanti, Esi; Septiawati, Laras (CV. Proaksara Global Transeduka, 2025)
This study will look at the impact of cash reserves and company size on corporate value (a case study of coal mining sub-sector businesses listed on the IDX between 2017 and 2022). In this study, 17 coal mining companies listed on the Indonesian stock exchange were chosen using a purposive sample method. This research uses quantitative data. The results of the statistical research indicate that cash reserves have a considerable impact on the value of the enterprises under consideration. This is demonstrated by the t-test results: 2.549 > t-table 1.668, significance 0.014 > 0.05. Thus, it can be determined that Cash Holding influences Company Value. The statistical analysis results indicate that Firm Size significantly influences Company Value in the examined companies. This is demonstrated by the t-value of -1.801 < t-table 1.668 and a significance of 0.078 > at a significance threshold of 0.05. As a result, it is reasonable to conclude that the Cash Holding variable has a large influence on Company Value. Cash reserves and firm size have a significant impact on the value of a firm. The f test confirms this, with a significance level of 0.021 < 0.05 and an f-value of 4.182 < f-table 3.134. This is demonstrated by the R Square value of 0.154, or 15.4%, with the remaining 84.6% influenced or clarified by parameters not examined in this study, such as Net Profit Margin, Return On Assets, and Debt To Equity Ratio.